ANALISIS TEKNIK PENGALAMATAN PADA WIRELESS SENSOR NETWORKS - Wiyanto, Eddy (Teknik dan Ilmu Komputer, 2012)
Wireless Sensor Networks consist of nodes which are able to perform sensing, computation, and communication. In many aspects, sensor networks are similar but also different from the mobile ad hoc networks (MANET). Their similarities include topology, shared communication medium, and connectivity problems. Different from the MANET, the sensor networks typically contain lower mobility, much more limited resources, which therefore lead to scalability problems. This paper discusses the addressing techniques for sensor networks, the trade-offs in the design of certain addressing scheme, and the comparison among various techniques. Â Keywords: wireless sensor networks, nodes, addresssing, wireless access media, RETRI